The crime of aggression under the authority of the security council - خلاف غودة; بن بوعبدالله نورة (مجلة الباحث للدراسات الأكاديمية, 2021)
The crime of aggression is considered one of the most controversial crimes, as it is a new name for an old crime, committed since ancient times, the attention to it clearly began since the end of World War II, as international efforts tried to define a concept for the crime of aggression and set legal mechanisms and procedures to combat it, except That this faced and encountered problems and Controversies for a long period of time, even after its inclusion in the list of international crimes and the adoption of its definition with the activation of the jurisdiction of the international criminal court over it in July 17, 2018, the Controversies still exist, especially as a necessary and binding procedures were stipulated exclusively to the Security Council over the crime of aggression, which established an exceptional authority of the security council over the crime of aggression.